ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PENGETAHUAN WUS TENTANG RISIKO TINGGI DALAM KEHAMILAN - Vega Muhida (Journal Of Applied Health Research And Development, 2022)
Background: Every pregnant woman has the potential for danger during pregnancy, childbirth, and postpartum. Until now, in all parts of the world, high-risk pregnancies are still a problem in health services, especially in developing countries. In Indonesia, the MMR decreased during the period 1991-2015 from 390 to 305 per 100,000 live births. However, this achievement is still far from the MDGs target of 102 per 100,000 live births. Until 2015 the target of the MDGs has not been achieved. While the target for the Sustainable Development Goals (SDGs), the MMR target is 70 per 100,000 live births in 2030. In relation to high-risk pregnancies, at the Kramatwatu Health Center there were 739 high-risk pregnancies found in 2021, while in the village of Pejaten, there are still many women of childbearing age who are pregnant or give birth at a risky age of 83. From these conditions, complications can result from high-risk pregnancies such as miscarriage, premature birth, genetic disorders and death. This can occur due to lack of knowledge about high-risk pregnancies. This research method is descriptive research with cross sectional or cross sectional design. This research was conducted in Pejaten Village, Kramatwatu Serang Banten. The research sample was taken by purposive sampling. Primary data collection was carried out using a questionnaire containing 25 questions filled out by respondents. In addition, the research output will be published in the Poltekkes journal (Jurnal of Applied Health). More than half (58.3%) of respondents still have less knowledge about high risk in pregnancy. Factors Age, education, occupation, history of pregnancy and sources of information related to the level of knowledge of wus about high risk in pregnancy. This research can help provide information to develop new strategies that are more appropriate in an effort to reduce high risk in pregnancy in the Kramatwatu Health Center area, especially in Pejaten village.